First molar eruption related to plaque acidogenicity in children of different socio-economic status - Delgado-Angulo, Elsa K. (2006)
Objective. The aim of this study was to evaluate the association between the eruption stage of the lower first permanent molar and dental plaque acidogenicity. Socio-economic status (SES), gender, and oral hygiene condition were also variables considered. Material and methods. 230 children between 6 and 8 years of age were recruited from one public and one private primary school with different SES in Lima, Peru. Clinical examinations were performed to assess lower first permanent molar eruption stage, plaque acidogenicity, and oral hygiene condition. Bivariate associations were analyzed through chi-square tests and the variable interactions were analyzed through a hierarchical log-linear analysis with backward elimination. Results. 21.8% of the population had highly acidogenic plaque, 34.3% acidogenic plaque, and 43.9% non-acidogenic plaque. Of the lower first permanent molars, 46.1% were fully erupted, whereas 53.9% were partially erupted. According to the final log-linear model, children with fully erupted molars and non-acidogenic plaque are less frequent in low than in high SES. Also, the frequency of children with partially erupted molars and acidogenic to highly acidogenic plaque is higher in males than in females. Finally, fully erupted molars and non-acidogenic plaque are more frequent in children with good hygiene than in children with moderate to poor hygiene. Conclusions. Association between eruption stage of the lower first permanent molar and plaque acidogenicity was not significant in a bivariate context. However, in a multivariate context, socio-economic status, oral hygiene condition, and gender had an impact on the association between the two main variables.